Water-Soluble Antitumor Agents. I. Synthesis and Biological Activity of 6-S-Aminoacyloxymethyl Mercaptopurine Derivatives - KASHIDA, Tatsuo; TANAKA, Takashi; TSUJIHARA, Kenji; NARASAKI, Naoko; OHOHASHI, Motoaki; HASHIYAMA, Tomiki; ODA, Kouji; HARADA, Naoyuki; HONGU, MITSUYA (Chemical & pharmaceutical bulletin, 1995)
In an attempt to improve the effectiveness and bioavailability of 6-mercaptopurine, various kinds of water-soluble analogues, such as 6-S-aminoacyloxymethyl mercaptopurine derivatives (3a-m) and 6-S, 9-disubstituted derivatives (7a, b and 9a, b), were synthesized. These compounds were evaluated for activity to augment antitumor immunity by using a double grafted tumor system. Antitumor activities against solid tumors (sarcoma 180 and colon 26) were also evaluated. Many compounds exhibited potent activities in both test systems. In particular, the aminopropionate derivative (3a) and the L-glutamate derivative (3f) showed significant enhancement of antitumor immunity together with potent antitumor activities.